Motivation Drives Employee Performance with Key Factors Revealed in Indonesia: Motivasi Mendorong Kinerja Karyawan dengan Faktor-Faktor Kunci yang Terungkap di Indonesia - Putri, Nova Permana; Ubaidillah, Hasan; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the effects of information technology use, innovative behavior, and motivation on employee performance at PT KAI Daop 8 Surabaya. Using quantitative methods, a sample of 103 employees was selected from a population of 159 through simple random sampling. Data were collected via structured questionnaires. Results indicate that information technology use, innovative behavior, and motivation each significantly enhance employee performance, with motivation being the most influential factor. These findings suggest that investing in technology, fostering innovation, and boosting motivation are key strategies for improving employee performance at PT KAI Daop 8 Surabaya. Highlight: Sample: 103 employees selected through simple random sampling. Significant Factors: Technology, innovation, and motivation improve performance. Key Influence: Motivation most significantly affects employee performance. Keyword: employee performance, information technology, innovative behavior, motivation, PT KAI Daop 8 Surabaya